2019
DOI: 10.1002/pds.4806
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported factors associated with the desire to continue taking sleep‐inducing drugs after hospital discharge: A survey of older adults

Abstract: Purpose To find out whether any prior experiences with sleep‐inducing drugs before hospitalization and positive experiences with these drugs during hospitalization influence a patient's wish to continue taking sleep‐inducing drugs after hospitalization. Methods We surveyed older hospital patients about use of sleep‐inducing drugs before, during, and after hospitalization and compared these answers with their hospital chart using the kappa statistic. The association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
0
8
1
4
Order By: Relevance
“…In a combined patient survey and chart review from the same hospital [14], 21% of the older patients had at least received one benzodiazepine during their hospital stay. We intended to lower this rate by 5 percentage points.…”
Section: Sample-size Calculation and Statistical Analysismentioning
confidence: 99%
“…In a combined patient survey and chart review from the same hospital [14], 21% of the older patients had at least received one benzodiazepine during their hospital stay. We intended to lower this rate by 5 percentage points.…”
Section: Sample-size Calculation and Statistical Analysismentioning
confidence: 99%
“…For example, a hospital chart review showed that 12% of all patients 65 and older received a Z-drug at least once during their stay [11]. A patient survey in the same hospital revealed that more than half of the older patients who received Z-drugs in the hospital wished to continue taking these drugs at home [12].…”
Section: Context: the Sleeping Pills Projectmentioning
confidence: 99%
“…Chart review studies give us an idea of how hospital doctors usually solve this conflict; they often prescribe benzodiazepines and newer non-benzodiazepines (so-called Z-drugs) for patients who have trouble sleeping [3][4][5]. While these drugs may help patients to sleep in the hospital environment, they also have adverse effects, such as confusion, falls, fractures, and craving [6] so they are not recommended for the treatment of transient sleep problems in most guidelines [7].…”
Section: Introductionmentioning
confidence: 99%
“…Weiterhin können sie kognitive Einschränkungen nach sich ziehen (Atkin, Comai & Gobbi, 2018). Schließlich kann die Erfahrung, mit Hilfe von Medikamenten einfach einschlafen zu können, einen ungünstigen Lernprozess für zukünftige Schlafprobleme anstoßen (Heinemann, Neukirchen, Nau, Hummers & Himmel, 2019) und eine dauerhafte Medikamenteneinnahme oder -abhängigkeit einleiten.…”
Section: Introductionunclassified